Seborgia cavernicola sp. nov. from a submarine cave on Okinawa Island, Ryukyu Islands, southwestern Japan (Crustacea, Amphipoda, Seborgiidae) - Shimomura, Michitaka; Fujita, Yoshihisa (Zootaxa, 2021)
A new seborgiid, Seborgia cavernicola sp. nov. is described from a submarine cave in Okinawa Island, Ryukyu Islands as the first record of the family from Japan. This species differs from its congeners by the following combination of characters: body without microspinules; eyes fainted, without ommatidia; epimeral plates with posterodistal angle produced into pointed process; main flagellum of antennule 4-articulate; article 2 of main flagellum of antennule longest; propodus of gnathopod 2 as long as wide; gland cone of antenna directed anteriorly; maxilla bilobed; uropod 3 biramous; and telson without setae and setules. A key to species of the genus is provided.